Hepatitis C infection among primary health care patients: prevalence and risk factors. (20th October 2021) - Ciupkeviciene, E; Dragunas, G; Dabravalskis, S; Petkeviciene, J; Kupcinskas, L
Abstract: Background: Many people chronically infected with the hepatitis C virus (HCV) are not aware of their infection. The benefit of screening for HCV is earlier treatment with antiviral medications, which are highly effective and can prevent long-term complications of chronic HCV such as cirrhosis, liver cancer, and death. This study aimed to examine the prevalence of HCV infection and its risk factors among primary health care patients. Methods: The study was carried out in the primary health care centre of seaport Klaipeda, Lithuania. Patients were invited to participate in the screening by family doctors, regional media, social networking sites, and leaflets. Screening for HCV involved a blood test for the presence of an antibody to HCV (TOYO rapid test). Those with positive test results and a randomly selected control group of patients with negative test results were invited to participate in a telephone interview about possible risk factors of infection. In total, 1720 patients were screened. The HCV infected group consisted of 32 patients (56.3% men, mean age 55.4±9.4 years) and a control group of 96 patients (55.2% men, mean age 54.8±9.5 years). Results: The prevalence of HCV infection among screened patients was 1.9%. The odds ratio (OR) of HCV infection in patients who reported blood transfusions before 1993 was 7.7 (95% CI 2.1-27.6) compared to those who did not have a blood transfusion or had later. HCV infection was diagnosed more often among patients who were blood donors before 1993 compared to those who were not donors or were later (OR 5.6; 95% CI 2.3-13.1). Having a tattoo increased the likelihood of HCV infection by 5.6 times (95% CI 2.1-14.4). Injection of illegal drugs was reported by 8.4% of HCV positive patients, 34.9% of them was in a prison for more than 3 months. Conclusions: Primary health care institutions should consider screening people who are at high risk of HCV infection. Key messages: Risky behaviours are associated with higher risk of HCV infection. Epidemiologic data on HCV infection is crucial for developing optimal healthcare policies for the prevention and treatment of HCV infection.